Morphological and Functional Changes of the Tibialis Anterior Muscle After Combined Mirror Visual Feedback and Electromyographic Biofeedback in Poststroke Patients: A Randomized Trial. (August 2021) - Liu, Meikuai; Xu, Leyi; Li, Haiyan; Chen, Shunping; Chen, Bin
Abstract : Objective: The aim of the study was to investigate the morphological and functional changes of the tibialis anterior muscle after mirror visual feedback combined with electromyographic biofeedback in poststroke patients. Design: A total of 46 poststroke patients were randomly divided into three groups: a mirror visual feedback + electromyographic biofeedback group, a mirror visual feedback group, and a control group. The mirror visual feedback + electromyographic biofeedback group was treated with both mirror visual feedback and electromyographic biofeedback, and the mirror visual feedback group was treated with mirror visual feedback alone. The morphological parameters, including the pennation angle, muscle thickness, and fascicle length, were assessed. Results: After 4 wks of treatment, the pennation angle and muscle thickness values were significantly increased in the mirror visual feedback + electromyographic biofeedback and mirror visual feedback groups ( P < 0.05). The increase of these values in the mirror visual feedback + electromyographic biofeedback group was significantly greater than that in both metrics in the mirror visual feedback and control groups ( P < 0.05), and those in the mirror visual feedback group were greater than those in the control group ( P < 0.05). There was no significant difference in the fascicle length value among the three groups as a result of the treatment. After the treatment, the neurological functions were all increased in three groups ( P < 0.05). Conclusions: A combination of mirror visual feedback and electromyographic biofeedback seems to be an effective therapy for improving the motor function of the tibialis anterior muscle in poststroke patients. Clinical trial registration number: ChiCTR1800017050. Abstract : Supplemental digital content is available in the text.